The relationship between academic achievement and motivation among secondary school pupils in selected Arab schools in Malaysia - Chafai, Yasmine (Usuli Faqih Research Centre PLT, 2023)
Motivation plays an important part in increasing academic performance, it all depends on how much work a student is willing to put in a subject, so, lack of motivation has been one of the most critical elements that influences student’s performance. The primary goal of this research was to examine the relationship between motivation and students’ academic achievement. The quantitative research approach was used in this study along with an adapted questionnaire developed by Pintrich et al (1991). A total of 300 Arab lower and upper secondary school pupils were selected to be the participants of this study by using simple random technique. The findings showed no evidence of a substantial relationship between motivation and the academic achievement of the Arab Schools Students (r= .06). It is advised to conduct additional research on the phenomenon of this study among Arab students utilizing various research methodologies. Keywords: Motivation, Academic, Achievement, Arab & Secondary, Schools